In vitro synergistic effect of Hibiscus sabdariffa aqueous extract in combination with standard antibiotics against Helicobacter pylori clinical isolates - Hassan, Sherif T S; Berchová, Kateřina; Majerová, Michaela; Pokorná, Marie; Švajdlenka, Emil (Pharmaceutical biology, 2016)
Context The increasing problem of drug-resistant strains has led to the failure of current treatment regimens of Helicobacter pylori (HP) infection. Recently, a new treatment strategy has been developed to overcome the problem by using natural products in combination with antibiotics to enhance the treatment efficacy. Objective The antimicrobial combinatory effect of the aqueous extract of Hibiscus sabdariffa L. (Malvaceae) (AEHS) with antibiotics (clarithromycin, CLA; amoxicillin, AMX; metronidazole, MTZ) has been evaluated in vitro against HP strains. Materials and methods Hibiscus calyces (35 g) were brewed in 250 mL of boiled water for 30 min, and minimum inhibitory concentrations (MICs) were determined by agar dilution method. The checkerboard assay was used to evaluate the antimicrobial combinatory effect according to the sum of fractional inhibitory concentration (∑FIC) indices. Results In this study, AEHS exerted remarkable bacteriostatic effect against all HP strains tested with MICs values ranging from 9.18 to 16.68 μg/mL. Synergy effect of AEHS with CLA or MTZ was obtained against four of seven HP strains tested with ∑FIC ranging from 0.21 to 0.39. The additive effect of AEHS with AMX was obtained against five of seven HP strains tested with ∑FIC ranging from 0.61 to 0.91. Conclusion This study presents AEHS as a potent therapeutic candidate alone, or in combination with antibiotics for the treatment of HP infection.
Keywords: Microbial Sensitivity Tests; klarithromycin; Plant Extracts; Humans; Metronidazole; Phytotherapy; fytoterapie; combinatory effect; Plants, Medicinal; Drug Synergism; mikrobiální testy citlivosti; Clarithromycin; lidé; antibakteriální látky; natural products; rostlinné extrakty; amoxicilin; Hibiscus; synergismus léků; Antimicrobial agents; Helicobacter Infections; Anti-Bacterial Agents; Helicobacter pylori; drug-resistant strains; Flowers; H. pylori infection; květy; Amoxicillin; léčivé rostliny; kombinovaná farmakoterapie; metronidazol; infekce vyvolané Helicobacter pylori; Drug Therapy, Combination